Human polyomaviruses genomes in clinical specimens of colon cancer patients. Issue 11 (15th February 2021) - Dolci, Maria; Signorini, Lucia; Toumi, Wafa; Basile, Giuseppe; D'Alessandro, Sarah; Ferrante, Pasquale; Delbue, Serena
Abstract: Colon cancer is the third cause of cancer death in the developed countries. Some environmental factors are involved in its pathogenesis, including viral infections. The possible involvement of human polyomaviruses (HPyVs) in colon cancer pathogenesis has been previously reported, leading to inconsistent conclusions. Clinical specimens were collected from 125 colon cancer patients. Specifically, 110 tumor tissues, 55 negative surgical margins, and 39 peripheral blood samples were analyzed for the presence of six HPyVs: JC polyomavirus (JCPyV), BK polyomavirus (BKPyV), Merkel cell PyV (MCPyV), HPyV −6, −7, and −9 by means of DNA isolation and subsequent duplex Real Time quantitative polymerase chain reaction. HPyVs genome was detected in 33/204 samples (16.2%): the significant higher positivity was found in tumor tissues (26/110, 23.6%), followed by negative surgical margins (3/55, 5.5%, p < .05), and peripheral blood mononuclear cells (PBMCs) (4/39; 10.3%). HPyVs load was statistically higher only in the tumor tissues compared to negative surgical margins ( p < .05). Specifically, MCPyV was detected in 19.1% (21/110) of tumor tissues, 3.6% (2/55) of negative surgical margins ( p < .05), and 7.7% (3/39) of PBMCs; HPyV‐6 in 2.7% (3/110) of tumor tissues, and 1.8% (1/55) of negative surgical margins; one tumor tissue (1/110, 0.9%) and one PBMCs sample (1/39, 2.6%) were positive for BKPyV; JCPyV was present in 0.9% (1/110) of tumor tissues. HPyV‐7 and 9 were not detected in any sample. High prevalence and load of MCPyV genome in the tumor tissues might be indicative of a relevant rather than bystander role of the virus in the colon tumorigenesis. Highlights: Colon cancer is the third cause of cancer death in Western countries and some evidences demonstrated that pathogens, like viruses, might be one of the risk factors for its pathogenesis. Little is known about the possible involvement of Human Polyomaviruses in colon cancer pathogenesis. The study is aimed to investigate the role of the Human Polyomaviruses in colon cancer pathogenesis. The results of the research indicate a high prevalence of Merkel Cell Polyomavirus genome in the tumor tissues that might be indicative of a relevant rather than bystander role of the virus in the colon tumorigenesis.